The eNanoMapper database for nanomaterial safety information - Jeliazkova, Nina; Chomenidis, Charalampos; Doganis, Philip; Fadeel, Bengt; Grafström, Roland; Hardy, Barry; Hastings, Janna; Hegi, Markus; Jeliazkov, Vedrin; Kochev, Nikolay; Kohonen, Pekka; Munteanu, Cristian R.; et al. (Beilstein Journal of Nanotechnology, 2015)
Background: The NanoSafety Cluster, a cluster of projects funded by the European Commision, identified the need for a computational infrastructure for toxicological data management of engineered nanomaterials (ENMs). Ontologies, open standards, and interoperable designs were envisioned to empower a harmonized approach to European research in nanotechnology. This setting provides a number of opportunities and challenges in the representation of nanomaterials data and the integration of ENM information originating from diverse systems. Within this cluster, eNanoMapper works towards supporting the collaborative safety assessment for ENMs by creating a modular and extensible infrastructure for data sharing, data analysis, and building computational toxicology models for ENMs.Results: The eNanoMapper database solution builds on the previous experience of the consortium partners in supporting diverse data through flexible data storage, open source components and web services. We have recently described the design of the eNanoMapper prototype database along with a summary of challenges in the representation of ENM data and an extensive review of existing nano-related data models, databases, and nanomaterials-related entries in chemical and toxicogenomic databases. This paper continues with a focus on the database functionality exposed through its application programming interface (API), and its use in visualisation and modelling. Considering the preferred community practice of using spreadsheet templates, we developed a configurable spreadsheet parser facilitating user friendly data preparation and data upload. We further present a web application able to retrieve the experimental data via the API and analyze it with multiple data preprocessing and machine learning algorithms.Conclusion: We demonstrate how the eNanoMapper database is used to import and publish online ENM and assay data from several data sources, how the “representational state transfer” (REST) API enables building user friendly interfaces and graphical summaries of the data, and how these resources facilitate the modelling of reproducible quantitative structure–activity relationships for nanomaterials (NanoQSAR).
Keywords: database; EU NanoSafety Cluster; nanoinformatics; nanomaterials; nanomaterials ontology; NanoQSAR; safety testing

(untitled) - Maynard, A. D.; Aitken, R. J.; Butz, T.; Colvin, V.; Donaldson, K.; Oberdörster, G.; Philbert, M. A.; Ryan, J.; Seaton, A.; Stone, V.; Tinkle, S. S.; Tran, L.; et al. (Nature, 2006)

Types and uses of nanomaterials, including safety aspects - European Commission (2012)

(untitled) - Cárdenas, W. H. Z.; Mamani, J. B.; Sibov, T. T.; Caous, C. A.; Amaro, E., Jr; Gamarra, L. F. (Int. J. Nanomed., 2012)

(untitled) - Kelder, T.; van Iersel, M. P.; Hanspers, K.; Kutmon, M.; Conklin, B. R.; Evelo, C. T.; Pico, A. R. (Nucleic Acids Res., 2012)

(untitled) - Mills, K. C.; Murry, D.; Guzan, K. A.; Ostraat, M. L. (J. Nanopart. Res., 2014)

(untitled) - Miller, A. L.; Hoover, M. D.; Mitchell, D. M.; Stapleton, B. P. (J. Occup. Environ. Hyg., 2007)

(untitled) - Gaheen, S.; Hinkal, G. W.; Morris, S. A.; Lijowski, M.; Heiskanen, M.; Klemm, J. D. (Comput. Sci. Discovery, 2013)

(untitled) - Marquardt, C.; Kühnel, D.; Richter, V.; Krug, H. F.; Mathes, B.; Steinbach, C.; Nau, K. (J. Phys.: Conf. Ser., 2013)

(untitled) - Kong, L.; Tuomela, S.; Hahne, L.; Ahlfors, H.; Yli-Harja, O.; Fadeel, B.; Lahesmaa, R.; Autio, R. (PLoS One, 2013)

2014 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) - Jeliazkova, N.; Doganis, P.; Fadeel, B.; Grafstrom, R.; Hastings, J.; Jeliazkov, V.; Kohonen, P.; Munteanu, C. R.; Sarimveis, H.; Smeets, B.; Tsiliki, G.; Vorgrimmler, D.; et al. (The first eNanoMapper prototype: A substance database to support safe-by-design, 2014)

Summary of the Spring 2014 NSC Database Survey - Mustad, A. P.; Smeets, B.; Jeliazkova, N.; Jeliazkov, V.; Willighagen, E. (2014)

(untitled) - Panneerselvam, S.; Choi, S. (Int. J. Mol. Sci., 2014)

European NanoSafety Cluster - Lynch, I. (Compendium of Projects in the European NanoSafety Cluster, 2014)

(untitled) - Jeliazkova, N.; Jeliazkov, V. (J. Cheminf., 2011)

(untitled) - Sansone, S.-A.; Rocca-Serra, P.; Field, D.; Maguire, E.; Taylor, C.; Hofmann, O.; Fang, H.; Neumann, S.; Tong, W.; Amaral-Zettler, L.; Begley, K.; Booth, T.; et al. (Nat. Genet., 2012)

(untitled) - Thomas, D. G.; Gaheen, S.; Harper, S. L.; Fritts, M.; Klaessig, F.; Hahn-Dantona, E.; Paik, D.; Pan, S.; Stafford, G. A.; Freund, E. T.; Klemm, J. D.; Baker, N. A. (BMC Biotechnol., 2013)

(untitled) - Roebben, G.; Rasmussen, K.; Kestens, V.; Linsinger, T. P. J.; Rauscher, H.; Emons, H.; Stamm, H. (J. Nanopart. Res., 2013)

2014 IEEE International Conference on Bioinformatics and Biomedicine (BIBM) - Rumble, J.; Freiman, S.; Teague, C. (The description of nanomaterials: A multi-disiciplinary uniform description system, 2014)

(untitled) - Abeyruwan, S.; Vempati, U. D.; Küçük-McGinty, H.; Visser, U.; Koleti, A.; Mir, A.; Sakurai, K.; Chung, C.; Bittker, J. A.; Clemons, P. A.; Brudz, S.; Siripala, A.; et al. (J. Biomed. Semantics, 2014)

(untitled) - Hastings, J.; Jeliazkova, N.; Owen, G.; Tsiliki, G.; Munteanu, C. R.; Steinbeck, C.; Willighagen, E. (J. Biomed. Semantics, 2015)

(untitled) - Hardy, B.; Douglas, N.; Helma, C.; Rautenberg, M.; Jeliazkova, N.; Jeliazkov, V.; Nikolova, I.; Benigni, R.; Tcheremenskaia, O.; Kramer, S.; Girschick, T.; Buchwald, F.; et al. (J. Cheminf., 2010)

(untitled) - Kohonen, P.; Benfenati, E.; Bower, D.; Ceder, R.; Crump, M.; Cross, K.; Grafström, R. C.; Healy, L.; Helma, C.; Jeliazkova, N.; Jeliazkov, V.; Maggioni, S.; et al. (Mol. Inf., 2013)

Towards the replacement of in vivo repeated dose systemic toxicity testing - European Commission (2013)

OpenAM - Thangasamy, I. (Packt Publishing Ltd., 2011)

(untitled) - Walkey, C. D.; Olsen, J. B.; Song, F.; Liu, R.; Guo, H.; Olsen, D. W. H.; Cohen, Y.; Emili, A.; Chan, W. C. W. (ACS Nano, 2014)

(untitled) - Vinken, M. (Toxicology, 2013)

(untitled) - Godwin, H.; Nameth, C.; Avery, D.; Bergeson, L. L.; Bernard, D.; Beryt, E.; Boyes, W.; Brown, S.; Clippinger, A. J.; Cohen, Y.; Doa, M.; Hendren, C. O.; et al. (ACS Nano, 2015)

(untitled) - Lynch, I.; Weiss, C.; Valsami-Jones, E. (Nano Today, 2014)

(untitled) - Klimisch, H.-J.; Andreae, M.; Tillmann, U. (Regul. Toxicol. Pharmacol., 1997)

Guidance on information requirements and chemical safety assessment - ECHA (Evaluation of available information, 2011)

The Problem of Data - Jahnke, L.; Asher, A.; Keralis, S. D. C. (Council on Library and Information Resources, 2012)

ECHA Dissemination site, Multi-Walled Carbon Nanotubes (MWCNT), synthetic graphite in tubular shape

(untitled) - Jaworska, J.; Nikolova-Jeliazkova, N. (SAR QSAR Environ. Res., 2007)

(untitled) - Jeliazkova, N.; Kochev, N. (Mol. Inf., 2011)

(untitled) - Nikolova, N.; Jaworska, J. (QSAR Comb. Sci., 2004)

(untitled) - Willett, P.; Barnard, J.; Downs, G. (J. Chem. Inf. Model., 1998)

(untitled) - Maggiora, G.; Vogt, M.; Stumpfe, D.; Bajorath, J. (J. Med. Chem., 2014)

(untitled) - Arts, J. H. E.; Hadi, M.; Irfan, M.-A.; Keene, A. M.; Kreiling, R.; Lyon, D.; Maier, M.; Michel, K.; Petry, T.; Sauer, U. G.; Warheit, D.; Wiench, K.; et al. (Regul. Toxicol. Pharmacol., 2015)

(untitled) - Gajewicz, A.; Cronin, M. T. D.; Rasulev, B.; Leszczynski, J.; Puzyn, T. (Nanotechnology, 2015)

D3: A JavaScript visualization library for HTML and SVG (2015)

ambit.js, Release 0.0.2 (E. Willighagen, 2015)

(untitled) - Rorabacher, D. A. (Anal. Chem., 1991)

Principles of Data Mining and Knowledge Discovery - Angiulli, F.; Pizzuti, C. (Fast Outlier Detection in High Dimensional Spaces, 2002)

Proceedings of the 17th International Conference on Pattern Recognition (ICPR’04) - Hautamaki, V.; Karkkainen, I.; Franti, P. (Outlier Detection Using k-Nearest Neighbour Graph, 2004)

A Practical Guide to Support Vector Classification - Hsu, C.-W.; Chang, C.-C.; Lin, C.-J.

(untitled) - Arora, M.; Bhambhu, L. (Int. J. Adv. Res. Comput. Sci. Software Eng., 2014)

(untitled) - Guazzelli, A.; Zeller, M.; Lin, W.-C.; Williams, G. (The R Journal, 2009)

(untitled) - Pechter, R. (ACM SIGKDD Explorations Newsletter, 2009)

(untitled) - Tcheremenskaia, O.; Benigni, R.; Nikolova, I.; Jeliazkova, N.; Escher, S. E.; Batke, M.; Baier, T.; Poroikov, V.; Lagunin, A.; Rautenberg, M.; Hardy, B. (J. Biomed. Semantics, 2012)

(untitled) - Hall, M.; Frank, E.; Holmes, G.; Pfahringer, B.; Reutemann, P.; Witten, I. H. (ACM SIGKDD Explorations Newsletter, 2009)

R: A language and environment for statistical computing - R Core Team (R Foundation for Statistical Computing, 2012)

(untitled) - Ooms, J. (arXiv, 2014)

R is hot - Smith, D.

(untitled) - Kim, J.; Wang, G.; Bae, S. T. (Int. J. Semantic Comput., 2014)

(untitled) - Chang, C.-C.; Lin, C.-J. (ACM Trans. Intell. Syst. Technol., 2011)

(untitled) - Sarimveis, H.; Alexandridis, A.; Bafas, G. (Neurocomputing, 2003)

(untitled) - Steinbeck, C.; Hoppe, C.; Kuhn, S.; Floris, M.; Guha, R.; Willighagen, E. L. (Curr. Pharm. Des., 2006)

(untitled) - Stewart, J. J. P. (J. Comput.-Aided Mol. Des., 1990)

(untitled) - Netzeva, T. I.; Worth, A.; Aldenberg, T.; Benigni, R.; Cronin, M. T. D.; Gramatica, P.; Jaworska, J. S.; Kahn, S.; Klopman, G.; Marchant, C. A.; Myatt, G.; Nikolova-Jeliazkova, N.; et al. (ATLA, Altern. Lab. Anim., 2005)

(untitled) - Jaworska, J.; Nikolova-Jeliazkova, N.; Aldenberg, T. (ATLA, Altern. Lab. Anim., 2005)

(untitled) - O'Boyle, N. M.; Banck, M.; James, C. A.; Morley, C.; Vandermeersch, T.; Hutchison, G. R. (J. Cheminf., 2011)

(untitled) - Gajewicz, A.; Schaeublin, N.; Rasulev, B.; Hussain, S.; Leszczynska, D.; Puzyn, T.; Leszczynski, J. (Nanotoxicology, 2015)

(untitled) - Schneider, C. A.; Rasband, W. S.; Eliceiri, K. W. (Nat. Methods, 2012)

(untitled) - Kanehisa, M.; Goto, S.; Sato, Y.; Furumichi, M.; Tanabe, M. (Nucleic Acids Res., 2012)

(untitled) - Kim, D.; Joung, J.-G.; Sohn, K.-A.; Shin, H.; Park, Y. R.; Ritchie, M. D.; Kim, J. H. (J. Am. Med. Inf. Assoc., 2015)

(untitled) - Ashburner, M.; Ball, C. A.; Blake, J. A.; Botstein, D.; Butler, H.; Cherry, J. M.; Davis, A. P.; Dolinski, K.; Dwight, S. S.; Eppig, J. T.; Harris, M. A.; Hill, D. P.; et al. (Nat. Genet., 2000)

(untitled) - Jeliazkova, N. (Expert Opin. Drug Metab. Toxicol., 2012)

Proceedings of the 22Nd International Conference on Software Engineering - Fielding, R. T.; Taylor, R. N. (Principled Design of the Modern Web Architecture, 2000)